2010
DOI: 10.1007/s11064-010-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate Release and Signalling in the Hippocampus

Abstract: The Ca(2+)-dependent release of aspartate from hippocampal preparations was first reported 35 years ago, but the functional significance of this process remains uncertain. Aspartate satisfies all the criteria normally required for identification of a CNS transmitter. It is synthesized in nerve terminals, is accumulated and stored in synaptic vesicles, is released by exocytosis upon nerve terminal depolarization, and activates postsynaptic NMDA receptors. Aspartate may be employed as a neuropeptide-like co-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Titration of purified protein in vitro (Fig. 1b) indicates an affinity of 107 ± 9 μM (s.d., n = 5) for glutamate, and 145 ± 18 μM ( n = 3) for aspartate (which has been identified as a co-neurotransmitter with glutamate in some neurons 24 ), and a pK a of 6.5 in the glutamate-bound and 7.0 in the ligand-free state (Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 98%
“…Titration of purified protein in vitro (Fig. 1b) indicates an affinity of 107 ± 9 μM (s.d., n = 5) for glutamate, and 145 ± 18 μM ( n = 3) for aspartate (which has been identified as a co-neurotransmitter with glutamate in some neurons 24 ), and a pK a of 6.5 in the glutamate-bound and 7.0 in the ligand-free state (Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, we observed that acute D-Asp administration also elicits a transient increase of extracellular L-Asp, without affecting the amount of this L-amino acid in homogenates. To explain this data, we suggest that abnormal accumulation of D-Asp in the brain may perturb one or more of the still unclear cellular mechanisms regulating the local racemization of D-Asp into L-Asp2829, L-Asp vesicular storage3031 and release32. In addition, we cannot exclude that non-physiological, high D-Asp extracellular concentration may displace L-Asp from its binding to L-Glu/L-Asp transporters, which regulate the uptake of both Asp enantiomers33, thus resulting in increased extracellular L-Asp levels.…”
Section: Discussionmentioning
confidence: 99%
“…* p < 0.05, one-way ANOVA plus Dunnett's test (A) or Holm-Sidak t test (B). (Gundersen, 2008;Nadler, 2011 …”
mentioning
confidence: 99%